Crimes against history - De Baets, Antoon 1955- (Routlege/Taylor & Francis Group, 2019)
"Crimes against History takes a global approach to the extreme forms of censorship to which history and historians have been subjected through the ages. The book is divided into two parts. Part 1 tells the tragic story of how the censorship of history has sometimes turned into deadly crimes against history, while Part 2 reverses the perspective and examines how the censorship of history has backfired. Comparing case studies from across the world and written from a human rights perspective, Crimes against History is an essential resource for anyone interested in how deeply history and politics influence each other, as well as for anyone wanting a fuller view of the history of history."--Provided by publisher.